Accuracy of four ultrasonography techniques in predicting histopathological classification of canine mammary carcinomas - Feliciano, Marcus Antonio Rossi [UNESP]; Ramirez, Ricardo Andrés Uscategui [UNESP]; Maronezi, Marjury Cristina [UNESP]; Maciel, Giovanna Serpa [UNESP]; Avante, Michelle Lopes [UNESP]; Senhorello, Igor Luiz Salardani [UNESP]; Mucédola, Talita [UNESP]; Gasser, Beatriz [UNESP]; Carvalho, Cibele Figueira; Vicente, Wilter Ricardo Russiano [UNESP] (Wiley, 2018)
Due to the importance of presurgical, noninvasive, and accurate diagnostic tools in mammary carcinoma characterization, this prospective secondary observational cohort study was designed to evaluate and compare the diagnostic accuracy of B-mode, Doppler, contrast enhancement ultrasonography, or acoustic radiation force impulse–elastography in identifying mammary carcinomas types with high degree of malignancy. A total of 246 mammary carcinomas from 141 female dogs were analyzed using B-mode, Doppler, contrast enhancement ultrasonography, and acoustic radiation force impulse ultrasonography prior to their histopathological classification according to types (simple, complex, or special) and grade (I, II, or III). Qualitative and quantitative variables were compared between carcinoma types and grades by Fisher's or analysis of variance. Diagnostic performance was estimated by receiver-operating characteristic analysis, using histopathological classification as a reference. Deformability (acoustic radiation force impulse) had a diagnostic specificity of 100% and sensitivity of 12% in identifying special carcinomas. A width:length ratio greater than 0.53 can be suggestive of special carcinoma, with 80% sensitivity and 76% specificity. Contrast wash-in and peak enhancement times lower than 7.5 and 13.5 s, respectively, were indicative of complex carcinoma at 62% sensitivity and 60% specificity. Contrast wash-in, peak enhancement, and wash-out times greater than 6.5, 12.5, and 64.5 s, respectively; were indicative of grade II and III carcinoma at 68% sensitivity and 62% specificity. In conclusion, B-mode ultrasonography, contrast enhancement ultrasonography, and acoustic radiation force impulse–elastography enabled the identification of some of the characteristics of high-grade mammary carcinoma types and grades in female dogs with limited accuracy. The findings from this study may contribute to oncology research and clinical management canine patients.
Keywords: canine; contrast-enhanced ultrasound; Doppler; elastography; tumors